The Reflection of the Crown: The Town of Chantada de Asma (Lugo) and the Urban Policy of the Kings of León and Castile (11th-14th Centuries) (Edad Media. Revista de Historia, 2026)
The town of Chantada (Lugo) is a medieval settlement founded by the king Alfonso IX of León. In this paper, we analyse the origins of the town and its urban council; as well as its relationship with its immediate surroundings: the county of Asma, subordinate to the county of Monterroso, and the alfoz of Chantada. All of this reflects the policies of the kings of León, Alphonse VII and Alphonse IX, as well as the subsequent presence of the royal family in the figures of the princes Sancho (the future Sancho IV) and Phillip of Castile.
Keywords: Chantada; Alfoz; Tenencia; Alfonso IX; Medieval urbanism